Selection of maize (Zea mays) hybrids for plant density tolerance - M S, ABD EL-ATY; EL-HITY, M A; AMER, E A; MOUSLHY, T T EL- (The Indian Journal of Agricultural Sciences, 2019)
Plant density tolerance (PDT) is one of the most important trait for breeders. The study was carried out at Sakha Research Station, Egypt in 2016. Half diallel crosses among 10 yellow maize (Zea mays L.) inbred lines were made. The resulting 45 hybrids and commercial check SC162 were evaluated under 2 nitrogen fertilizer levels (N1= 286 and N2=357 kg N/ha) and 3 plant densities (D1=59351 plant/ha, D2=71846 plants/ha and D3=84341 plant/ha) in 2017 to identify the superior hybrids at high plant densities and estimate combining ability variance and effects at various plant densities for grain yield. The mean squares due to nitrogen fertilizer (N) was not significant, while the mean squares due to plant density (D), N×D interaction, hybrids (H), H × N, H × D and H × N × D were highly significant. Also the mean squares due to general combining ability (GCA) and specific combining ability (SCA) and their interactions with N, D, and N×D were highly significant. SCA or non-additive gene action was the main influence in the inheritance and was more affected by N, D and N×D interaction for grain yield. The best inbred lines for GCA effects, viz. P3, P8 and P10 can be used in maize breeding program to give high yield in various environmental conditions especially for plant density tolerance. The best hybrids for SCA effect under most environments especially high plant densities were P1 × P3, P1 × P8, P2 × P6, P4 × P5, P4 × P8, P5 × P7 and P8 × P10. The hybrid P8 × P10 had high significant positive superiority. These hybrids can be upgraded to other stages of evaluation in the maize breeding program, especially for plant density tolerance.